Science, Technology, and Society: Entangled, not intractable (KULT_online, 2014)
The volume Science and Technology Studies. Eine sozialanthropologische Einführung, edited by Stefan Beck, Jörg Niewöhner and Estrid Sørensen, takes a closer look at important threads, positions, and concepts of the heterogeneous field of study called Science and Technology Studies (STS). In addition to this 'cartography’ of the STS from an explicitly social-anthropological perspective, the authors focus on the theoretical and conceptual as well as on methodical and methodological interfaces between the research programmes of STS and Social and Cultural Anthropology.